Administrating Kinship: Marriage Impediments and Dispensation Policies in the 18th and 19th Centuries - Lanzinger, Margareth (Brill, 2023)
From the late eighteenth century, more and more men and women wished to marry their cousins or in-laws. This aim was primarily linked to changes in marriage concepts, which were increasingly based on familiarity. Wealthy as well as economically precarious households counted on related marriage partners. Such unions, however, faced centuries-old marriage impediments. Bridal couples had to apply for a papal dispensation. This meant a hurdled, lengthy and also expensive procedure. This book shows that applicants in four dioceses - Brixen, Chur, Salzburg and Trent - took very different paths through the thicket of bureaucracy to achieve their goal. How did they argue their marriage projects? How did they succeed and why did so many fail? Tenacity often proved decisive in the end.